The role of self-efficacy in contraceptive use among early married women in Jember - Lylyan Amalia Mia Septya; Devi Arine Kusumawardani (Jurnal Ners dan Kebidanan Indonesia)
Background: The Family Planning Program (FP) is an integrated part of the national development program whose achievements are realized through contraception. One district that has not fulfilled those targets is Silo District which has a prevalence of user contraception by 72.88% in 2021, as well as the top three ranks in the prevalence of early marriage in Jember regency for 2020-2022. Contraceptive use behavior, especially among women who marry at an early age, is influenced by self-efficacy. Self-efficacy includes self-abilities and belief in making decisions and dealing with certain tasks. Objectives: This study was to analyze the relationship between self-efficacy with the use of contraception in women who marry at an early age in Silo District, Jember Regency Methods: Cross-sectional quantitative study conducted in Silo District, Jember Regency. The sample was obtained by 93 using the simple random sampling method. Contingency coefficient test (α<0,05) with the help of SPSS software before being presented in text and tables. The respondents were interviewed using the self-efficacy questionnaire, which was adopted from Bandura’s theory, with 18 questions. The questionnaire was then categorized as high self-efficacy and low self-efficacy. Results: The majority of early married women used contraceptives (92.5%), and most of the women used injection contraception (60.5%). The research found a high relationship between self-efficacy and contraceptive use (p-value=0.000), and the correlation coefficient was 0.707. Conclusions: This study concludes that self-efficacy has a relationship with a marked strong coefficient correlation and direction relationship positively related to contraception among women who married early in Silo District, Jember Regency. Therefore, the health workers in health facilities need to improve the implementation and supervision of prevention of early marriage programs by establishing cooperation with related services such as the Department of Religion to increase socialization about contraceptive use and prevention of unintended pregnancy among early marriage couples.